ANALISIS ENERGI DAN EKSERGI PADA SISTEM ROTARY KILN RKC-2 PT. SEMEN BATURAJA - Sati, Adinda Lara; Anugrah, Rendotian; Safaruddin, Safaruddin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
The cement industry is one of the energy-intensive industries because of the large amount of energy used. The cost used for energy consumption in a cement factory is about 20-30% of the total cost of cement production (UNIDO, 1994). In the cement production process, the raw mill preparation and clinker production stages are the stages that require the most energy. Energy conservation in the rotary kiln system affects the optimization of production costs. One method of identification on energy conservation is through energy and exergy analysis. In this analysis, energy loss and exergy were identified based on the calculation of mass balance, energy, enthalpy, entropy and exergy. Based on the analysis, the value of energy efficiency is greater than exergy efficiency. The energy and exergy efficiency of the rotary kiln system are 79.40% and 57.10%, respectively. The energy and exergy efficiency of the rotary kiln unit are 64.93% and 50.48%, respectively. The exergy efficiency value in the rotary kiln system is greater than the rotary kiln unit because there is energy utilization at the outlet of the suspension preheater and cooler. The greatest energy and exergy efficiency occurred at the maximum clinker mass flow rate and minimum coal mass flow rate. Irreversibility of rotary kiln units and systems RKC-2 PT. Semen Baturaja Palembang are 49.52% and 42.9%, respectively.